2015
DOI: 10.1111/spol.12195
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Social Insurance Participation and Generosity: Do Firm Characteristics Matter?

Abstract: Income inequality in China has been much documented and debated. However, one important aspect of income inequality – social insurance inequality – has been largely understudied. We use a large national panel of firm data to examine the possible influence of various firm characteristics on the inequalities in social insurance participation and generosity in the period 2004–07. Our findings reveal substantial ownership sector and regional gaps in social insurance provision by firms, with the private domestic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Hukou has been discussed as an institutional constraint on social insurance participation in several empirical studies. Moreover, various studies based on city-level surveys and national panel data showed that the members of the informal sector labour force who are employed by private enterprises or who are self-employed, particularly migrant workers without local hukou , are unlikely to be covered by employment-based social insurance programmes in urban China (Gao et al , 2012; Park et al , 2012; Chen and Gallagher, 2013; Giles et al , 2013; Gao and Rickne, 2015). These findings are consistent with those of other similar household surveys in Shanghai (Nyland et al , 2006) and Jiangsu Province (Nielsen et al , 2005).…”
Section: Institutional Constraints and Self-selection Behaviourmentioning
confidence: 99%
“…Hukou has been discussed as an institutional constraint on social insurance participation in several empirical studies. Moreover, various studies based on city-level surveys and national panel data showed that the members of the informal sector labour force who are employed by private enterprises or who are self-employed, particularly migrant workers without local hukou , are unlikely to be covered by employment-based social insurance programmes in urban China (Gao et al , 2012; Park et al , 2012; Chen and Gallagher, 2013; Giles et al , 2013; Gao and Rickne, 2015). These findings are consistent with those of other similar household surveys in Shanghai (Nyland et al , 2006) and Jiangsu Province (Nielsen et al , 2005).…”
Section: Institutional Constraints and Self-selection Behaviourmentioning
confidence: 99%
“…The less educated are more likely to access informal jobs that have weaker labour protection, leading to their low participation in contributory social security schemes. From the market/employer perspective, “retaining skilled workers has long been considered an important motive for employer provision of non‐wage benefits” (Gao and Rickne, 2017, p. 761). Labour‐intensive enterprises often use a dual strategy to reward highly educated workers with social insurance benefits while capping total labour costs by excluding the rest of their workers from contributory schemes (Nielsen et al, 2005; Nyland, Thomson and Zhu, 2011).…”
Section: Access Barriers To Contributory Pension Coveragementioning
confidence: 99%
“…To be frank, savings in the bank are more secure; who knows how our contribution has been spent!”. Studies based on quantitative data have shown a negative effect of rural hukou on migrant workers’ pension coverage (Gao, Yang and Li, 2012; Gao and Rickne, 2017; Park, Wu and Du, 2012; Jiang, Qian and Wen, 2018).…”
Section: Access Barriers To Contributory Pension Coveragementioning
confidence: 99%
See 1 more Smart Citation
“…This is exacerbated by the fact that, as discussed below, contribution collection has been the responsibility of different agencies. Studies have indicated that the enforcement of social insurance coverage is very relaxed in many areas (Nyland et al, 2006; Matra et al, 2007; Rickne, 2013; Gao and Rickne, 2014 and 2017). This has led to a situation where many workers are not, in practice, covered and where social insurance contributions are paid on the basis of wages that are lower than those actually being paid.…”
Section: Population Ageing and The Urban Employees’ Pension Programmementioning
confidence: 99%